Analisa Pengoperasian Cargo Hold Bilges System dalam Mencegah Terjadinya Flooding di MV. Meratus Malino - Muhammad Rizki Afrizal Azhar; Supangat Supangat; Kuncowati Kuncowati (Populer: Jurnal Penelitian Mahasiswa, 2024)
This research aims to analyze the operation of the Cargo Hold Bilges System in preventing flooding on MVs. Meratus Malino. Researchers conducted this research while conducting a Sea Practitioner (PRALA) for 12 months starting from January 29 2023 to February 5 2024 on board the MV. Meratus Malino is a container carrier type ship managed by the shipping company PT. The Meratus Line operates domestic shipping services on the route Jakarta-Surabaya-Makassar-Bitung-Anggrek (North Gorontalo)-Surabaya-Jakarta-Bawean-Jakarta-Semarang. The population in this study was the MV crew. Merastus Malino consisted of 20 people, while the sample was the crew of the MV ship. Meratus Malino who is in charge or has responsibility for operating the Cargo Hold Bilges System totals 16 people consisting of the MV deck crew. Meratus Malino totaling 9 people and MV engine crew. Meratus Malino numbered 7 people. This research method uses a qualitative method using a descriptive approach, while for the data source the researcher uses secondary data sources, while the data collection instruments are questionnaires, field studies and interviews. The results of this research show that in operating the Cargo hold Bilges system, a system and several components such as the bilge pump, ejector, seachast valve, injection valve connected to the bilge pump and hydraulic valve are needed which can function properly and more optimally in ship operational activities. . And to prevent flooding in the hold, it is necessary to check the hold regularly and if you see standing water in the hold, immediately make an order to empty the hatch so that the hatch is dry and the cargo remains protected from flooding in the hold.